Implementing numerical simulation for static and dynamic loading of cable-stayed Penang Bridge - Mohammed, Mohammed Idris (2016)
Penang (I) bridge is classified as a Cable stayed bridge, which constructed globally for their long spans and aesthetics appealing. Factors such as high traffic volumes and geometrical movements cause increase in deflections and stresses on the bridge system, which at the end these defects possibly lead to degrade their service life cycle. Due to these reasons, Penang (I) bridge needs continuous monitoring i.e. a tool to resist any changes toward various loading conditions, such as sensors arrangement. Hence, the study aims to recommend sensors positions for Penang (I) bridge, by conducting modal analysis and simulation processes which introduced in the Finite Element Method (FEM). In addition, specific software called, ‘Nastran & Patran’ was used to compute the displacement, forces and stresses based on static symmetrical and unsymmetrical loading conditions, as well as mode shapes on dynamic loading condition. As a result, from these analyses, critical elements and their associated grids points of the bridge elements were identified, which eventually, sensors placement have been proposed. The results revealed there are 78 sensors can be placed at the entire structures, which are mainly located at the cables, towers and end side spans and main spans of the bridge. In term of contribution, the study noticed the complexity of Penang (I) bridge structures coupled with high traffic volumes might lead to damages at invisibles locations, which only can be identified using the finite element analysis. Therefore, the proposed sensors for the bridge probably can be used by the relevant authorities and perhaps as guidelines for future references.